Evaluation of the New 8th Grade Mathematics Textbook Computerized,and Non- Computerized, Activities From Teachers' Points of View - Muneer Jebreel Karama, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The study aims to evaluate the computerized, and non- computerized activities in the new Palestinian mathematics’ textbook for 8th grade according to the point of view of teachers who taught with the book during the last semester and who have long years of experience in teaching mathematics. The researcher developed a new framework from a literature review that was used to evaluate mathematics, computerized activities in the 8th grade textbook. The analysis for this paper was conducted with data using quantitative and qualitative methods, an interview & a questionnaire. The questionnaire, which was utilized for this study, consisted of 23 indicators and a 5- point LIKERT scale in light of the framework, 2 Mathematics, teachers interviewed in semi-structured method. A tool of this study validated by a group with expertise in teaching math and tested through CRONBACH’S alpha (0.84). Seventy-two teachers participated in the study, and they select through purposeful sampling using a voluntary process. They contacted through email and Face-book Messenger and provided with a link for the questionnaire designed on a Google Drive sheet. The general result shows a neutral evaluation of the computerized activities, and the same results confirmed through a semi- structured interview. The results showed no significant differences due to gender or years of experience as a teacher, while there were differences between the types of schools, with the government and UNRWA schools on the one hand and private schools on the other. However, the evaluation was a below average for the following indicators: open-ended problems, the induction method, ICT (such as using smart devices), and the simplicity of the language used for computerized activities. In light of these results, the researcher recommends that computerized activities that were rated below average be enriched and that gaps be bridged.